Frontispiece: Synthesis of Ajoene Analogues by Novel Synthetic Strategies. Issue 9 (10th February 2021) - Yamamoto Raynbird, Marina; Khokhar, Shaista S.; Neef, Daniel; Evans, Gareth J. S.; Wirth, Thomas
Abstract : Garlic ( Allium sativum ) has a long history as a food ingredient and traditional medicine, and garlic extracts have been known for a very long time to exhibit a wide range of biological properties (some general structures of ajoene analogues are shown on the picture of the plant). In their Full Paper on page 3008, Wirth et al. describe the synthesis of three non‐natural Allium analogues. These analogues were biologically evaluated in their ability to inhibit biofilm production in S. Aureus and P .  Aeruginosa with promising results.